The Influence of Fintech Payment on The Faculty of Economics Students' Financial Management Behavior - Sembiring, Dhea Fitriana Rosalia; Dewi, Meutia; Tantawi, Rahmad (Doktoral Ilmu Manajemen, Universitas Pasundan, 2023)
This research aims to determine the effecttrust in fintech payment services, benefits of fintech payment services and ease of fintech payment serviceson the financial management behavior of students at the Faculty of Economics, Samudra University. The sample in this study consisted of 91 students. The data analysis method used is multiple linear regression analysis, t test, F test and coefficient of determination. The regression equation is Y = 1.533 + 0.063X1 + 0.361X2 + 0.202X3.trust in fintech payment services, benefits of fintech payment services and ease of fintech payment servicespartially has a significant effect on financial management behavior.trust in fintech payment services, benefits of fintech payment services and ease of fintech payment servicessimultaneously has a significant effect on financial management behavior. Adjusted R2 is 0.350. That is, variabletrust in fintech payment services, the benefits of fintech payment services and the ease of fintech payment services influenceFinancial management behavior of students at the Faculty of Economics, Samudra University is 35%, while the remaining 65% is influenced by other variables outside this research model.